Amplitude scintillation effects on SAR. Issue 6 (1st July 2014) - Belcher, David P.; Cannon, Paul S.
Abstract : Space‐based low‐frequency synthetic aperture radar (SAR) is affected by the ionosphere, which induces both phase and amplitude fluctuations, known as scintillation, into the radar signal. This paper describes the effect of amplitude scintillation on SAR imagery. The two‐way amplitude and intensity probability density functions (pdf) for both monostatic and bistatic SAR are derived from the one‐way Nakagami‐m distribution. The moments are then used to determine the SAR radiometric calibration error and image contrast from the one‐way S 4 index. It is also shown that monostatic SAR experiences an S 4 ‐dependent radar cross‐section (RCS) enhancement that is not experienced by bistatic SAR. The anisotropy of the ionospheric irregularities strongly affects the degree to which amplitude scintillation will be visible in SAR imagery. The description of anisotropic effects is reviewed and extended to cover SAR. The variation over the Earth is illustrated, showing that a sun‐synchronous satellite will experience the strongest effect near Brazil. Two PALSAR images of the same area of Brazilian rainforest are compared, one of which shows azimuthal streaking, corresponding to an amplitude modulation of ± 1 dB. The one‐way S 4 index is determined from this imagery using both the RCS enhancement and image contrast measures of S 4, which produce similar results.